Development of automated patch clamp assays to overcome the burden of variants of uncertain significance in inheritable arrhythmia syndromes - Ma, Joanne G.; Vandenberg, Jamie I.; Ng, Chai-Ann (Frontiers in Physiology, 2023)
Advances in next generation sequencing have been exceptionally valuable for identifying variants in medically actionable genes. However, for most missense variants there is insufficient evidence to permit definitive classification of variants as benign or pathogenic. To overcome the deluge of Variants of Uncertain Significance, there is an urgent need for high throughput functional assays to assist with the classification of variants. Advances in parallel planar patch clamp technologies has enabled the development of automated high throughput platforms capable of increasing throughput 10-to 100-fold compared to manual patch clamp methods. Automated patch clamp electrophysiology is poised to revolutionize the field of functional genomics for inheritable cardiac ion channelopathies. In this review, we outline (i) the evolution of patch clamping, (ii) the development of high-throughput automated patch clamp assays to assess cardiac ion channel variants, (iii) clinical application of these assays and (iv) where the field is heading.